2020
DOI: 10.1371/journal.pone.0243749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the implementation of the HIV Treat All guidelines on key ART treatment outcomes in Namibia

Abstract: Background This study aimed to help the Namibian government understand the impact of Treat All implementation (started on April 1, 2017) on key antiretroviral therapy (ART) outcomes, and how this transition impacts progress toward the UNAIDS’s 90-90-90 HIV targets. Methods We collected clinical records from two separate cohorts (before and after treat-all) of ART patients in 10 high- and medium-volume facilities in 6 northern Namibia districts. Each cohort contains 12-month data on patients’ scheduled appoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…Almost all participants (95.7%) initiated ART after a median time of 5 days, which is consistent with recent data reported in Namibia [ 32 ]. In addition to the clinical benefits for the patients themselves, this is a very positive result for HIV transmission prevention [ 4 , 33 , 34 ], given that the participants reported frequent anal sexual intercourse with men, and frequent condomless anal intercourse.…”
Section: Discussionsupporting
confidence: 90%
“…Almost all participants (95.7%) initiated ART after a median time of 5 days, which is consistent with recent data reported in Namibia [ 32 ]. In addition to the clinical benefits for the patients themselves, this is a very positive result for HIV transmission prevention [ 4 , 33 , 34 ], given that the participants reported frequent anal sexual intercourse with men, and frequent condomless anal intercourse.…”
Section: Discussionsupporting
confidence: 90%
“…Haiti’s level of same-day ART after T&S policy adoption (45.0%) compared favorably to the level found in a global survey of ART access in LMICs (38.4%) ( 14 ) but was lower than that observed in Botswana, Kenya, and Malawi (57.1%, 63.6%, and 69.5%) ( 15 , 16 ). The trend toward early HIV diagnosis and rapid ART for those with WHO stage 1 and 2, following adoption of T&S in Haiti, was similar to the trend documented in Namibia following policy change ( 17 ).…”
Section: Discussionsupporting
confidence: 64%
“…Other studies have consistently reported lower VLS among men in Rwanda 6,18,19 . In Namibia, although the country achieved the 90‐90‐90 targets by 2020, lower VLS among men delayed achievement of these targets 20–22 . Men, in general have been reportd to have lower uptake of HIV services.…”
Section: Discussionmentioning
confidence: 97%
“…6,18,19 In Namibia, although the country achieved the 90-90-90 targets by 2020, lower VLS among men delayed achievement of these targets. [20][21][22] Men, in general have been reportd to have lower uptake of HIV services. This pattern is also observed in key hard-to-reach groups among men, for example, men who have sex with men (MSM).…”
Section: Discussionmentioning
confidence: 99%